Nonverbal Behavior in Face-to-face Survey Interviews: An Analysis of Interviewer Behavior and Adequate Responding. Issue 1 (February 2022) - Foucault Welles, Brooke; Sun, Hanyu; Miller, Peter V.
We examine relationships between interviewers' nonverbal behaviors and adequate responding in face-to-face survey interviews. We videotaped professional interviewers administering face-to-face survey interviews and coded them for three interviewer nonverbal behaviors: smiling, nodding, and direct gaze. These nonverbal interviewer behaviors were associated with significant increases in the frequency of respondents' adequate responses. Moreover, the nonverbal behaviors were equally likely to present in standardized and unstandardized utterances. These results suggest that interviewers' nonverbal behaviors positively correlate with adequate responding without deviating from standardized interview protocols. We discuss implications for survey theory and interviewer training.